PENINGKATAN KERJA SAMA TIM PADA MURID KELAS III MELALUI TEAMS GAMES TOURNAMENT (TGT) BERBASIS PERMAINAN KARTU INTERAKTIF - Nur laili, Aditya; Nur Kumala, Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve teamwork skills and learning outcomes of third-grade elementary school students through the implementation of the Teams Games Tournament (TGT) cooperative learning model assisted by interactive card games. The study was motivated by students' low level of teamwork during the learning process. Most students tended to learn individually, were less active in group discussions, and had difficulty sharing responsibilities effectively when working in groups. These conditions resulted in low learning participation and unsatisfactory learning outcomes. This study employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The research subjects were 28 third-grade students in the 2026/2027 academic year. Data were collected through observations of teamwork activities, learning achievement tests, documentation, and field notes. The data were analyzed using descriptive quantitative and qualitative approaches by comparing the results of each cycle. The findings revealed that the implementation of the Teams Games Tournament (TGT) model assisted by interactive card games effectively improved students' teamwork skills and learning outcomes. Teamwork activities increased from the fair category in Cycle I to the very good category in Cycle II. In addition, the percentage of students achieving mastery learning exceeded the predetermined success criteria. The interactive card games created an enjoyable learning environment, increased students' participation in group discussions, strengthened peer communication, and fostered responsibility within the team. Therefore, the Teams Games Tournament (TGT) cooperative learning model assisted by interactive card games can be considered an effective alternative learning strategy to improve teamwork skills and learning outcomes among third-grade elementary school students.